ANALISIS KELAYAKAN INVESTASI PERUSAHAAN PERKEBUNAN PT. LADANG SAWIT KENDAWANGAN DI KABUPATEN KETAPANG - KOMARIYATI, RIDHWAN, ANI MUANI, (Jurnal Social Economic of Agriculture, 2018)
Investments in oil palm plantations should be carefully and thoroughly, because the large funding needs and continuous fund spending. The research goal is to determine the feasibility investment Ladang Sawit Kendawangan Plantation on condition decline of CPO and Kernel selling prices. This reseach used a combination of secondary data from relevant agencies and primary data by collecting some opinions from the plantation Manager and  Ladang Sawit Kendawangan Plantation employee subdistrict Kendawangan in Ketapang.The analysis method used is the investment criteria analysis which consists Net Present Value (NPV), Internal Rate of Return (IRR), Net B / C Ratio, Payback Periods and Sensitivity Analysis. The results from analysis feasibility of PT. Ladang Sawit Kendawangan Plantation an area of 2,485 Ha are still feasible, the feasibility level is indicated by the value of NPV  Rp 56,553,315,900 for 25 years earning period, IRR 22.05%, Net B / C ratio 1.24 and a payback period 4.6 years, The results of the sensitivity analysis with three scenarios: 1) a decrease in the price of CPO and Kernel 10%. 2) 10% increase in input costs. and 3) a decrease and cost increase of respectively 10%, showed the plantation is still feasible.Keywords : Investment Feasibility, Sensitivity analysis, Ladang Sawit Kendawangan Plantation